Exploiting Voicing Cues for Contrast Enhanced Frequency Shaping of Speech for Impaired Listeners - HARTE, NAOMI (IEEE, 2006)
This paper investigates the use of voicing information as an additional cue in contrast enhanced frequency shaping (CEFS) of speech to improve perception in the hearing impaired. The presented work builds on an existing system combining multiband compression with contrast enhanced frequency shaping (MICEFS) to restore the auditory nerve response of a hearing impaired listener. CEFS can improve the perception of voiced segments. Hence voicing cues are used to differentiate segments for processing. Alternative processing for unvoiced segments is investigated and shown to improve neural representation of unvoiced segments compared to using MICEFS processing alone.
PUBLISHED
Keywords: Electronic & Electrical Engineering